Geomicrobiological Characterization of the Evaporitic Ecosystem in the Hypersaline Lake Laguna Verde (Andean Puna, Northwestern Argentina) - Saona-Acuna, L (John Wiley and Sons Ltd, 2024)
Laguna Verde s dome-shaped structures are distinctive formations within the Central Andes, displaying unique geomicrobiological features. This study represents a pioneering investigation into these structures, assessing their formation, associated taxa, and ecological significance. Through a multifaceted approach that includes chemical analysis of the water body, multiscale characterization of the domes, and analysis of the associated microorganisms, we reveal the complex interplay between geology and biology in this extreme environment. The lake s alkaline waters that are rich in dissolved cations and anions such as chloride, sodium sulfate, and potassium, coupled with its location at the margin of the Antofalla salt flat, fed by alluvial fans and hydrothermal input, provide favorable conditions for mineral precipitation and support for the microorganism s activity. Laguna Verde s dome-shaped structures are mainly composed of gypsum and halite, displaying an internal heterogeneous mesostructure consisting of three zones: microcrystalline, organic (orange and green layers), and crystalline. The green layer of the organic zone is predominantly composed of Proteobacteria, Bacteroidetes, and Cyanobacteria, while the orange layer is mostly inhabited by Cyanobacteria. The results of the study suggest that oxygenic photosynthesis performed by Cyanobacteria is the main carbon fixation pathway in the microbial community, supported by carbon isotopic ratios of specific biomarkers. This finding highlights the important role played by Cyanobacteria in this ecosystem. © 2024 The Authors. Ecology and Evolution published by John Wiley & Sons Ltd.